Analisis Makna Kawā’ib dalam Al-Qur’an (Kajian Semantik Toshihiko Izutsu) - Monica, Salma; Dasuki, Akhmad; Faridatunnisa, Nor (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The term kawā'ib is mentioned once in the Koran in surah al-Nabā 'verse 33. The term kawā'ib in al-Qur'an and the translation means plump girls. This